Polybrominated diphenyl ether contamination in sediments from rivers in the western Niger Delta of Nigeria - Iwegbue, Chukwujindu M A; Oshenyen, Ejonafuvwe V; Peretiemo-Clarke, Beatrice O; Olisah, Chijioke; Nwajei, Godwin E; Martincigh, Bice S (Marine pollution bulletin, 2024)
This study investigated the concentrations of 39 polybrominated diphenyl ether (PBDE) congeners in sediments from three rivers in the western Niger Delta of Nigeria that have been affected by pollution from urbanization and industrial activities. The Σ39 PBDE concentrations in sediments from these rivers ranged from 0.29 to 95.5, 5.15 to 121, and 0.73 to 66.1 ng g-1 for the Afiesere (AR), Edor (ER), and Okpare Rivers (OR), respectively. The homologue distribution patterns indicated the prominence of tetra- and penta-BDE congeners in sediments from these rivers. The ecological risk assessment results showed that the penta-BDEs were the primary source of risk to sediment-dwelling organisms in these rivers. However, the human health risk assessment indicated negligible risks for exposure of both adults and children to PBDEs in these sediments. The source apportionment suggests that the PBDE contamination in these river sediments was derived from long-distance migration, debromination of highly brominated congeners, and commercial penta-BDEs. These results reflect the use of penta-BDE formulations in this region rather than octa- and deca-BDE formulations.
Keywords: monitorování životního prostředí; River systems; Halogenated Diphenyl Ethers; hodnocení rizik; Sediments; lidé; Polybrominated diphenyl ethers; Geologic Sediments; řeky; halogenované difenylethery; Water Pollutants, Chemical; Nigeria; Niger Delta; Nigérie; Rivers; Environmental Monitoring; chemické látky znečišťující vodu; Risk Assessment; Humans; geologické sedimenty